2017
DOI: 10.1002/tox.22440
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilver particles increase follicular atresia: Correlation with oxidative stress and aromatization

Abstract: Present study was performed in order to update the possible mechanism(s), involving in nanosilver particles (NSPs)-induced detrimental impacts in ovarian tissue. For this purpose, 24 mature female rats were divided into control and 0.5, 1, 5 mg/kg NSPs-received groups (intraperitoneally, for 35 days). Follicular growth and atresia, ovarian total antioxidant capacity (TAC), malondialdehyde (MDA), superoxide dismutase (SOD) contents, serum estrogen (E ) level and macrophages infiltration were investigated. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…The detected alterations in such hormonal levels are indicative for an abnormal reproductive axis function. These findings are in line with some previous reported data obtained with other kinds of NMs, that is, Ni-, 17 TiO 2 -, 16 Ag-, 20 and NP-rich diesel exhaust, 15 while are in conflict with other investigations which demonstrated opposite hormonal response trend 13,19 or failed to detect significant changes in sex hormone levels after NM exposure. 14,18 These different results may be due to the features of NMs used in the studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The detected alterations in such hormonal levels are indicative for an abnormal reproductive axis function. These findings are in line with some previous reported data obtained with other kinds of NMs, that is, Ni-, 17 TiO 2 -, 16 Ag-, 20 and NP-rich diesel exhaust, 15 while are in conflict with other investigations which demonstrated opposite hormonal response trend 13,19 or failed to detect significant changes in sex hormone levels after NM exposure. 14,18 These different results may be due to the features of NMs used in the studies.…”
Section: Discussionsupporting
confidence: 88%
“…This is one of the most important reproductive endpoints that have already been investigated by several in vivo studies using different types of NMs (Table 1). [13][14][15][16][17][18][19][20] Indeed, the knowledge gained from the assessment of hormonal changes serves as a foundation for investigations focused on evaluating NMs as potential endocrine-disrupting toxicants. 12…”
Section: Introductionmentioning
confidence: 99%
“…This inhibition did not permanently affect the cells since cell proliferation increased again after the removal of the nanosilver [ 148 ]. Female Wistar rats treated with an intraperitoneal injection of 50–60 nm nanosilver resulted in decreased angiogenesis in the ovarian tissue visualized via immunofluorescence [ 149 ]. In a wound healing study using NHDF cells and NHEK cells, decreased production of VEGF was seen for both low and high treatment concentrations of 10 nm nanosilver, indicating decreased angiogenesis, with a greater inhibition of VEGF production seen in NHEK cells [ 90 ].…”
Section: Nanosilver and Angiogenesismentioning
confidence: 99%
“…Previous studies have shown the presence of macrophages in any phase of follicular development (Katabuchi et al ., 1996; Wu et al ., 2004). In atretic follicles, GCs in apoptosis might stimulate a recruitment of macrophages as reported in atretic follicles induced by nanosilver particles (Mirzaei et al ., 2017).
Figure 3Apoptosis of granulosa cells (GCs) of atretic follicles from rat ovaries after eCG stimulation observed in ovarian sections stained by H&E ( A , B ) and immune labelling for cleaved caspase-3 by avidin–biotin–peroxidase method ( C , D ).
…”
Section: Resultsmentioning
confidence: 99%